Halogenases of Qarhan Salt Lake in the Qaidam Basin: Evidence From Halite Fluid Inclusions - Li, Jun; Zhang, Xiying; Hu, Mingyue; Li, Wenxia; Miao, Weiliang; Yuan, Xiaolong; Li, Yongshou; Tang, Qiliang; Han, Wenxia; Ma, Haizhou (Frontiers in Earth Science, 2021)
The fluid inclusion composition of halite can help track chemical composition of ancient fluids and, thus, serves as a reliable index to analyze ancient brine in salt lakes. Qarhan Salt Lake (QSL) is the largest potash brine deposit in China. Although the mixing of modern river water and Ca-Cl deep water is widely accepted as potassium formation, the mixing characteristics in the time domain and driving factors of deep water are still unclear. Here, the chemical composition of fluid inclusions in primary halite samples collected from the ISL1A borehole in QSL was measured by LA-ICP-MS technology. The analysis results show that, during the formation stage of the S4 salt layer in QSL, the main potassium salt layer, the contents of Ca2+ and Sr2+ in brine increased significantly. There is evidence confirming that Ca-Cl deep water is beneficial to the enrichment of potassium and the surrounding rivers generally develop terraces. It suggests that, during the formation stage of the QSL potassium salt layer, more Ca-Cl inflow water of the northern margin supplies the salt lake, inferring that it was driven by tectonic activities. In addition, the chemical composition of halite fluid inclusions shows that there is an anomaly in geochemistry at the early stage of salt formation in QSL. By combining the time of tectonic activities, it is inferred that the anomaly is not caused by tectonic activities but maybe caused by a salt-forming event. This work indicates that deep water and tectonic movement have a huge impact on the evolution of salt lakes. Therefore, it is necessary to consider the influence of deep water and tectonic activities on the salt-forming evolution stage of salt lakes when studying the salt-forming evolution stage of salt lakes and paleoclimate by using salt lake deposition.